Isolation and Antimicrobial Activities of Phytochemicals from Parinari curatellifolia (Chrysobalanaceae) - Phillip Mawire; Winnie Mozirandi; Matthias Heydenreich; Godloves Fru Chi; Stanley Mukanganyama (Hindawi Limited, 2021)
The widespread use of antimicrobial agents to treat infectious diseases has led to the emergence of antibiotic resistant pathogens. Plants have played a central role in combating many ailments in humans, and Parinari curatellifolia has been used for medicinal purposes. Seven extracts from P. curatellifolia leaves were prepared using serial exhaustive extraction of nonpolar to polar solvents. The microbroth dilution method was used to evaluate antimicrobial bioactivities of extracts. Five of the extracts were significantly active against at least one test microbe. Mycobacterium smegmatis was the most susceptible to most extracts. The methanol and ethanol extracts were the most active against M. smegmatis with an MIC of 25 µg/mL. The hexane extract was the most active against Candida krusei with an MIC of 25 µg/mL. None of the extracts significantly inhibited growth of Klebsiella pneumoniae and Staphylococcus aureus. Active extracts were selected for fractionation and isolation of pure compounds using gradient elution column chromatography. TLC analyses was carried out for pooling fractions of similar profiles. A total of 43 pools were obtained from 428 fractions. Pools 7 and 10 were selected for further isolation of single compounds. Four compounds, Pc4963r, Pc4962w, Pc6978p, and Pc6978o, were isolated. Evaluation of antimicrobial activities of Pc4963r, Pc4962w, and Pc6978p showed that the compounds were most active against C. krusei with MFC values ranging from 50 to 100 µg/mL. Only Pc6978p was shown to be pure. Using spectroscopic analyses, the structure of Pc6978p was determined to be β-sitosterol. The antifungal effects of β-sitosterol were evaluated against C. krusei in vitro and on fabrics. Results showed that β-sitosterol reduced the growth of C. krusei attached to Mendy fabric by 83%. Therefore, P. curatellifolia can be a source of lead compounds for prospective development of novel antimicrobial agents. Further work needs to be done to improve the antifungal activity of the isolated compound using quantitative structure-activity relationships.